Blind frequency tracking based on time-domain spreading for MB-OFDM-UWB systems - Li-jun GE; Hong WU (Tongxin xuebao)
A blind carrier frequency offset (CFO) tracking algorithm based on time-domain spreading (TDS) was proposed for multiband orthogonal frequency division multiplexing ultra wide band systems.The scheme uses data symbols and the mapped TDS ones to develop time and frequency-domain estimators and tracking loops respectively.Simulation results indicate that the proposed scheme has a better performance in tracking accuracy than pilots-aided ones.Under the SNR of 10dB,the mean square root errors of the residual CFO reach 2 10-4,and the bit error rate of the system is 10-6× of magnitude.